Perbedaan Derajat Osteoartritis Sendi Lutut pada Hasil Radiografi Posisi AP Supine dan AP Erect di Instalasi Radiologi Rumah Sakit Akademis Jaury Jusuf Putera Makassar - A.AR.Rakhmansya Iskandar; Rusman Achmad; Imran Amin (Lontara Journal of Health Science and Technology, 2020)
Osteoarthritis is a degenerative joint disease that is associated with damage to joint cartilage. One way to diagnose mild pain or the onset of OA early is to do a rontgen examination. The aim of the study was to determine the differences in the degree of osteoarthritis of the knee joint AP position erect with the AP supine position. This research was conducted in the hospital. Academic Jaury Jusuf Putera Makassar April - June 2019. This type of research is descriptive analytical, data collection techniques using questionnaires, sampling techniques carried out by accidental sampling analysis. Data analysis using statistics Presentation of data is presented in the form of graph tables accompanied by narration. Based on the results of the study it can be concluded that the Erect Position has an assessment score with an average of 7.20 while the Supine position with an average of 8.00. From the results of the statistical test obtained p value (0.455)> 0.05 means that there is no statistically significant difference in scores between Erect and Supine positions. It is expected that the radiology officer chooses the right projection that is in accordance with the patient's general condition. If it is possible for the patient to be examined with the projection of AP Weight-Bearing Standing, the officer uses the projection, otherwise the officer can use the AP Supine or AP Erect position because the two positions have no significant differences based on the results of the existing research.